THEMATIC PROGRESSION IN STUDENTS’ DESCRIPTIVE TEXTS - Mega Wati Dewi; Khauriena Fratami Hernawan; Yanuarti Apsari (PROJECT (Professional Journal of English Education), 2019)
This research aims to find out types of thematic progression pattern used by students in writing descriptive text and to know the dominant thematic progression used in students’ writing descriptive text. This research employed a descriptive-qualitative research design. The respondents of the research were eleven grade students of SMKN 1 Cimahi. The data collection was documentation. The source of the data was descriptive texts written by students of Instrumentasi Otomatisasi Process-D. There were 9 texts written by the respondents. The collected data was analyzed by using the theory from Bloor & Bloor (2013) as the theoretical to analyze the data. The result of this research found that students used three types of Thematic Progression in students’ writing descriptive text, they are Constant Theme, Linear Theme, Split Rheme. Furthermore, Constant Theme is the most frequent themes used in students’ writing descriptive text.